Joseph Conrad's "The Secret Sharer": the shadow and the process of individuation (a Jungian reading) - Koohestanian, Farhang; Omar, Noritah (Universiti Malaya, 2009)
In contemporary literary theory, Joseph Conrad has been a frequent subject of new historical and postcolonial studies. Due to the settings and the characters in his works, as well as the fact that the stories take place in Africa and the East, postcolonial critics have investigated his novels, Heart of Darkness and Lord Jim in particular, from a postcolonial perspective and have tried to unveil hidden angles and enhance the understanding of his works by applying terminology specific to the field.